FAKTOR-FAKTOR YANG MEMPENGARUHI LUARAN PADA PASIEN PERDARAHAN SUBARAKHNOID: PENELITIAN COHORT PROSPEKTIF 18 BULAN - Muhlisa, Safitri; Ramadhoni, Pinto Desti; Junaidi, Achmad; Octavinawaty, Lenny; Adwirianny, Ashita Hulwah (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Introduction: Subarachnoid hemorrhage (SAH) is an acute bleeding in the subarachnoid space. The mortality rate of SAH is quite high and survivors will experience limitations in activity daily living. Identification and factors that affect SAH are needed to improve patient outcomes. Aim: to identify the factors that affect the mortality of SAH Methods: This study was an observational study with a prospective cohort approach regarding the factors that affect the outcome of subarachnoid hemorrhagic patients in Dr. Mohammad Hoesin Hospital Palembang from January 2021 to July 2022. Results: From 62 subjects, the patients were 55.35 (SD ± 12.4) years old in average, most of them were female (67.7%). About 87.1% of patients had GCS> 8 (mean 11.68, SD ± 3.273). There were 82.3% of patients with mild-moderate NIHSS (mean 11.68; SD ± 3.273). The mortality rate was 37.1% (n = 23) with associated factors such as onset of admission (p = 0.044, GCS on admission (p= 0.003), severity of stroke (NIHSS) (p = 0.013), SAH severity (Hunt and Hess scale) (p=0.00), modified fisher scale (p=0.000), and coiling (p=0.001).The factor that most influenced the outcome was modified Fisher 3-4 (OR= 12,426, CI95% = 2,239 – 68,953) and non-coiling (OR: 12,2278, CI95% = 1,716 – 87,838). Discussion: There was a significant correlation between admission onset, GCS on admission, stroke severity (NIHSS score), modified Fisher scale, SAH severity (Hunt and Hess scale), and coiling, with the mortality of subarachnoid hemorrhage. Modified fisher scale and non-coiling were the most dominant factors that affected the mortality rate. Keywords: SAH, mortality, outcome